Histoenzymatic Study on Spleen of Kadaknath Fowl - Dharve, Anar Singh (Indian Journal of Veterinary Anatomy, 2020)
Histoenzymatic study was conducted on spleen of twenty five Kadaknath fowl from day old to thirty weeks of age. These birds were sacrificed ethically and spleen were collected. Spleen tissue was processed for routine procedure of histoenzymatic studies (alkaline phosphatase, acid phosphatase and adenosine tri phosphatase). Alkaline phosphatase activity was moderate to intense in capsule of spleen in all age groups showing an increasing trend with the advancement of age. Connective tissue capsule covering the spleen showed moderate to intense acid phosphatase activity in almost all the age groups. Moderate adenosine triphosphatase activity was noticed in capsule of spleen in group I and it gradually increased as age advances. Negative acid phosphatase activity was seen in red pulp, whereas in white pulp the activity was increasing with the advancement of age. Alkaline phosphatase and adenosine tri phosphatase activity was mild in red pulpwhereas in white pulp these activities were moderate to intense.